Miamia maimai n. sp., a new Pennsylvanian stem-orthopteran insect, and a case study on the application of cladotypic nomenclature - O. Béthoux; J. Gu; Y. Yue; D. Ren (Fossil Record, 2012)
A new stem-orthopteran insect assignable to the – traditional – genus and the – cladotypic-defined – taxon Miamia Dana, 1864 is described based on abundant material collected from the Xiaheyan locality (Ningxia, China; Early Pennsylvanian). Intra-specific wing venation variability in Miamia maimai n. sp. is appreciated based on wing pairs of single individuals, and on a complete series of conditions. Rare variants are reported. Details of head and leg morphology are documented: the new species possesses a five-segmented tarsus provided with paired claws and arolium, and labial palps with at least four segments, probably five. The nomenclatural section is conducted under the cladotypic nomenclatural procedure, but in a way largely consistent with the traditional usage. This experiment demonstrates that a combination composed of a "genus level-taxon" name previously associated with a definition and type material (e.g. Miamia), a specific epithet (e.g. maimai), and authorship information (e.g. Béthoux et al. 2012), with further mention to "Miamia maimai" or "M. maimai", provides a suitable reference to the species under all nomenclatural procedures, including the traditional one.doi:10.1002/mmng.201200008